(untitled) (Research, Society and Development, 2021)
Based on the critical discourses analysis, this study reached the goal of thinking about what was said and not said concerning the attributes of masculinity and femininity that configure the modes of management in organizations. This research is based on the analysis of discourse as the objective of understanding the meaning of the enunciation by means of the enunciative marks given and not mentioned. Eight semi-structured interviews were conducted based on a guiding script. A technique used to select the subjects was the snowball. What was said by four male managers and four female managers confirms that for women the male attributes are best suited for the management, and for men feminine attributes as emotional involvement and commitment contribute to a more humanized management. What is implied is that the male predominance in management positions is due to the inability of women conquer the professional spaces as men, because they do not have the right genetic heritage or because they need to be protected by men, who are ‘natural born leaders’.